Use of Radiopharmaceuticals for Diagnosis, Treatment, and Follow-Up of Differentiated Thyroid Carcinoma - Frederik A. Verburg; Bart de Keizer; Johannes W. van Isselt (Anti-Cancer Agents in Medicinal Chemistry, 2007)
In 1942, Dr. Seidlin of the Memorial Hospital in New York was faced with a 51-year- old patient who had undergone a thyroidectomy in 1923 [1]. At the time, the histologic diagnosis was a ‘malignant adenoma’ of the thyroid. In 1938 the patient returned with overt signs of thyroid hyperfunction (hyperthyroidism) and lower back pain. A metastasis was found in the lower spine, and surgically removed. Over the next years the patient remained hyperthyroid and developed more bone metastases. At the time of presentation to Dr. Seidlin, the patient was in an extremely poor condition: he was in severe pain, severely hyperthyroid, and severely underweight. At this time radioiodine therapy had just reached the clinical arena. In 1937 Hertz, Roberts and Evans investigated the rabbit's thyroid function using I-128 [2]. Later they pursued therapeutic goals for e.g. Graves' disease using I-130. They used dosages that we now know would have been merely diagnostic if it were not for a probable 10% I-131 contaminant [3]. Livingood and Seaborg identified I-131 as a separate isotope. In 1942 two groups independently reported on the successful treatment of hyperthyroidism with I-131 sodium iodide [4,5]. Radioiodine was so rare that it was recovered from the urine, purified and re-administered to the patient. The patient responded favourably to the radioiodine treatment, and he received several more courses of I-131. Geiger-counter examination of the patient revealed two previously unknown metastases, thereby indicating the diagnostic capabilities of radioiodine. The patient did very well on these courses: the hyperthyroidism subsided, the body-weight kg increased from 38 to 53 kilograms, and the pains diminished. This report of a potential cure for terminally ill patients fuelled the public imagination to a degree that it hit the political agenda. Effective on August 1, 1946, the Atomic Energy Act (AEA) made radioisotopes available for medical use in the USA. This date marks the beginning of ‘atomic medicine’, later named nuclear medicine.
Keywords: Thyroid Hormone